“A Qualitative Analysis of the Media Representation of CEO pay in the UK in the wake of the 'Shareholder Spring'” - Rywczuk, Kasian (2012)
This dissertation investigates the topic of executive remuneration and its portrayal in the media in the wake of the “shareholder spring.” It is a UK based qualitative analysis which uses NVivo 10 software to conduct a content analysis across three different newspaper publication websites, for 12 events over a two year period.